Russia before and after Crimea : nationalism and identity 2010-17 - Kolstø, Pål; Blakkisrud, Helge (Edinburgh University Press Ltd, 2018)
Russia's annexation of Crimea in 2014 brought East - West relations to a low. But, by selling the annexation in starkly nationalist terms to grassroots nationalists, Putin's popularity reached record heights. This volume examines the interactions and tensions between state and societal nationalisms before and after the annexation.
"Our research project organised a capstone conference at Tallinn University 28-29 April 2016, and most of the chapters in the current volume were first presented as papers at that conference."--Page xvii
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Russo-Ukrainian War, 2014- -- Influence -- Congresses.; Russia (Federation) -- History -- 1991- -- Congresses.; Guerre russo-ukrainienne, 2014- -- Influence -- Congrès.; Russie -- Histoire -- 1991- -- Congrès.; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; HISTORY -- North America.; Influence (Literary, artistic, etc.); Russia (Federation); Since 1991; Electronic books.; Conference papers and proceedings; History